The Physicochemical Characteristics of Oil Palm Residue-Clay Biocomposite For Removing Food Colouring in Water - Padmanaban, Logithavani; Yunus, Zalilah Murni (Enhanced Knowledge in Sciences and Technology, 2023)
The demand for synthetic food colouring in food industries has been increasing due to its low cost as compared to natural colourant. Sunset yellow (SY) is one of the most utilized synthetic food colouring in food industries to add colour into beverages, sweets, ice cream, jams, jelly, condiments and other foods. Presence of sunset yellow residues in discharge water from food industries is capable of harming living organism. Adsorption techniques by using biodegradable adsorbent have been used as an effective method to remove these contaminant from water. This research involve preparation of biochar derived from oil palm residue reinforced with clay. The physicochemical characteristics of this clay biocomposite was investigated. The characterization of adsorbent has displayed the presence of functional groups by FTIR. The concentration of solution before and after the treatment with clay biocomposite was determined with UV-VIS spectroscopy. The maximum removal efficiency was observed at pH 4, 5 mg/L of solution concentration. The adsorption has reached equilibrium after 30 min of contact time between adsorbent and adsorbate. The pseudo-second kinetic order (R2=0.981) and Langmuir isotherm model (R2=0.9598) were well fitted to the adsorption data.